Red LED photobiomodulates the metabolic activity of odontoblast-like cells - De Almeida, Leopoldina De Fátima Dantas [UNESP] (2016)
Phototherapy has been indicated as an adjunctive treatment for tissue repair, including the pulp tissue. However, there are no defined irradiation parameters, which is a great challenge to the clinical use of phototherapy. The aim of this study was to evaluate the effect of phototherapy with red LED on odontoblast-like MDPC-23 cells, using different parameter settings. Cells were seeded (104 cells/cm²), incubated for 12 h in complete DMEM and then the culture medium was replaced by DMEM supplemented with 0.5% FBS. After 12 h incubation, irradiations were performed (630±10 nm) using a LEDTable device with a 20 or 40 mW/cm² power density and 2 J/cm² energy dose. The cells were irradiated 1 or 3 times, at 1 min intervals. Non-irradiated cells served as control. The cells were evaluated for viability (MTT assay), total protein dosage (Lowry method) and number of viable cells (Trypan blue). The data (n=12 per group) were submitted to Kruskal-Wallis and Mann-Whitney tests (p=0.05). A single irradiation with 20 or 40 mW/cm² enhanced cell viability, which was negatively affected after 3 consecutive irradiations. Cells irradiated only once with 20 mW/cm² produced more proteins compared with those irradiated with 40 mW/cm². Reduction in the number of viable cells occurred only after 3 consecutive irradiations with 40 mW/cm². In conclusion, red LED was capable of biomodulating the metabolic activities of cultured MDPC-23 odontoblast-like cells. The best cell biostimulation was obtained when a single irradiation with 2 J/cm2 energy dose and 20 mW/cm2 power density was delivered to the pulp cells.